Smartphone and video games overuse effects on hand joints: time for screening interventions?. (27th May 2018) - Megna, M.; Gisonni, P.; Balato, N.
Abstract : Linked article: This article is commented on by N. Kluger, p. e457 in this issue. To view this article visithttps://doi.org/10.1111/jdv.15053